Strategi Promosi Prodi Pendidikan Sendratasik Dalam Meningkatkan Jumlah Mahasiswa - Fajry, Fajry; Annur, Saipul; Handayani, Tutut (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
Promotion as a communication strategy is expected to be able to introduce and attract public interest in an educational institution, including the Sendratasik Education study program. This research aims to find out the strategies used in carrying out educational promotions to increase the number of students. This study uses a qualitative method. Data collection was collected through observation, interviews, and documentation. Meanwhile, data reduction, data presentation, and data verification are strategies for analyzing data. The results of this research are: In its implementation, the promotion of the Sendratasik Education Study Program uses advertising, direct marketing, and socialization promotion strategies. The promotion strategy carried out by the Sendratasik Education study program also uses social media such as Instagram, Facebook, and YouTube. The Sendratasik Education Study Program also holds festival activities ranging from music festivals to cultural introductions. These activities are a form of promotional strategy carried out by the Sendratasik Education Study Program.